Providing optimal care for active youth in Canada - Laura Purcell; Sarah Campos; Michael Dickinson; Graham Thompson; Tatiana Jevremovic (Canadian Medical Education Journal, 2022)
Sports are important activities for youth, with millions of children and adolescents participating in organized sports and recreational activities every year. Sports participation has many benefits but can also cause injuries, accounting for two-thirds of all injuries in Canadian adolescents and resulting in hundreds of thousands of medical visits annually. Despite the frequency of sports-related injuries in youth, many practising pediatricians are not comfortable managing these issues, citing a lack of teaching and clinical exposure during training.  Many studies have found deficits in musculoskeletal (MSK) and sport and exercise medicine (SEM) training in residency programs in North America, including Canadian pediatric residency programs. To address this learning gap, Canadian pediatric residency programs should incorporate more MSK/SEM training and clinical exposure to these issues.  A standardized national curriculum in MSK/SEM will help ensure that community pediatricians practicing in Canada are adequately prepared to care for active youth.